Discrimination and stigmatization of people living with hiv/aids: literature review (2014)
The HIV/AIDS pandemic is a problem that encompasses multiple fields on a personal and social level, influencing both the infected person and the social network he/she develops in. The Stigma appears as a very important problem for those people who live with HIV/AIDS don´t look after treatment, don´t disclose their serostatus and isolate from society, widely deteriorating quality of life. The paper begins with a review of the literature using various databases. In total 43 articles were selected. Health professionals appear as important actors for people living with HIV/AIDS (PLHA), as they provide support and help at several levels (including medical and personal ones), and any stigmatizing attitude expressed by them has a great impact, from there the importance of identifying and correcting any negative aspect even since academic training, through the inclusion of HIV–related content in the curriculum both undergraduate and continuing education.